XWare: a middleware for prognostics and health management in education (2020)
Prognostics and Health Management (PHM) is a maintenance strategy that allows for the prediction of the productivity and health of manufacturing systems. Because of the advantages of implementing PHM strategies, tools and platforms focused on PHM education become important. Work on creating such a tool exists in XRepo, a big data architecture that allows for the sharing of experimental data between educators and students. This work proposes the XWare architecture, a PHM education middleware that bridges gap between sensor data acquisition and the XRepo-provided data storage solution. The joint architecture of both XWare and XRepo is thus denominated PHM-Edu. The development of XWare involved the definition of education-focused requirements, the creation of a conceptual framework, and the instantiation of the framework with specific technological solutions and interfaces. This study found that the implemented XWare architecture performs well in low-cost hardware, and that (when paired with XRepo) it allows for a...